2014
DOI: 10.1038/ismej.2014.32
|View full text |Cite
|
Sign up to set email alerts
|

Predictive modeling of gingivitis severity and susceptibility via oral microbiota

Abstract: Predictive modeling of human disease based on the microbiota holds great potential yet remains challenging. Here, 50 adults underwent controlled transitions from naturally occurring gingivitis, to healthy gingivae (baseline), and to experimental gingivitis (EG). In diseased plaque microbiota, 27 bacterial genera changed in relative abundance and functional genes including 33 flagellar biosynthesis-related groups were enriched. Plaque microbiota structure exhibited a continuous gradient along the first principa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
164
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(179 citation statements)
references
References 47 publications
13
164
1
1
Order By: Relevance
“…Furthermore, the assumption that only old plaque causes gingival bleeding does not take the microbiological characteristics of the plaque biofilm into account. Studies relating oral plaque microbiota to gingival inflammation do exist, but these evaluate total plaque or saliva rather than the old and young portions of plaque separately [29, 30]. A recent cross-sectional study in orally healthy participants has reported that the correlation between plaque and bleeding scores on average is low [31].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the assumption that only old plaque causes gingival bleeding does not take the microbiological characteristics of the plaque biofilm into account. Studies relating oral plaque microbiota to gingival inflammation do exist, but these evaluate total plaque or saliva rather than the old and young portions of plaque separately [29, 30]. A recent cross-sectional study in orally healthy participants has reported that the correlation between plaque and bleeding scores on average is low [31].…”
Section: Discussionmentioning
confidence: 99%
“…Perturbations of oral microbiota are associated with many common dental conditions, including periodontal disease (4), gingivitis (5,6), and dental caries (7). A number of studies show statistical associations between poor oral health and coronary heart disease (8), endocarditis, preterm birth (9), and exacerbations of existing chronic conditions, such as diabetes and osteoporosis (10), although whether these associations are causal is uncertain.…”
mentioning
confidence: 99%
“…From the results (Figure 8) we found that the distribution of taxa Streptococcaceae, Actinomycineae, Micrococcineae and Prevotellaceae had significant different between gingival status (Wilcoxon Rank-sum Test P-value < 0.001). Among them, Prevotellaceae was abundant in gingivitis samples (I and E), while other three taxa were abundant in healthy samples (B), which has also been verified by the previous works in Huang, et al, 2014 [26]. We also measured the correlation between the taxa pattern and the MGI and calculated the Pearson correlation coefficient (R).…”
Section: Case Study 3: Study On Oral Microbial Communities Of Differementioning
confidence: 90%
“…150 samples were collected from 50 hosts' saliva in 3 stages: naturally occurring gingivitis (I), healthy gingivae (B) and experimental gingivitis (E) by Huang, et al, 2014 [26]. The Mazza Gingival Index (MGI) of each stage for the host was recorded to reflect the gingival conditions from medical aspect.…”
Section: Case Study 3: Study On Oral Microbial Communities Of Differementioning
confidence: 99%